Proteome alterations in gamma-irradiated human T-lymphocyte leukemia cells - Szkanderová, Sylva; Vávrová, Jirina; Hernychová, Lenka; Neubauerová, Vera; Lenco, Juraj; Stulík, Jirí (Radiation research, 2005)
Analyses of the protein expression profiles of irradiated cells may be beneficial for identification of new biomolecules of radiation-induced cell damage. Therefore, in this study we exploited the proteomic approach to identify proteins whose expression is significantly altered in gamma-irradiated human T-lymphocyte leukemia cells. MOLT-4 cells were irradiated with 7.5 Gy and the cell lysates were collected at different times after irradiation (2, 5 and 12 h). The proteins were separated by two-dimensional electrophoresis and quantified using an image evaluation system. Proteins exhibiting significant radiation-induced alterations in abundance were identified by peptide mass fingerprinting. We identified 14 proteins that were either up- or down-regulated. Cellular levels of four of the proteins (Rho GDP dissociation inhibitor 1 and 2, Ran binding protein 1, serine/threonine protein kinase PAK2) were further analyzed by two-dimensional immunoblotting to confirm the data obtained from proteome analysis. All identified proteins were classified according to their cellular function, including their participation in biochemical and signaling pathways. Taken together, our results suggest the feasibility of the proteome method for monitoring of cellular radiation responses.
Keywords: signální transdukce; proteom; upregulace; imunoblotting; Signal Transduction; 2D gelová elektroforéza; Humans; Gamma Rays; Up-Regulation; T-Lymphocytes; Down-Regulation; záření gama; lidé; počítačové zpracování obrazu; down regulace; Image Processing, Computer-Assisted; časové faktory; barvení stříbrem; leukemie T-buněčná; Silver Staining; Electrophoresis, Gel, Two-Dimensional; nádorové buněčné linie; poškození DNA; DNA Damage; Immunoblotting; Proteome; T-lymfocyty; Cell Line, Tumor; Leukemia, T-Cell; hmotnostní spektrometrie; Time Factors; Mass Spectrometry